Information and Communication Technologies in Behavioral Health A Literature Review with Recommendations for the Air Force - Breslau, Joshua (RAND Corporation, 2015)
The dramatic evolution in information and communication technologies (ICTs) online and on smartphones has led to rapid innovations in behavioral health care. To assist the U.S. Air Force in developing a strategy for use of ICTs, the authors reviewed the scientific literature on applications of ICTs to prevent and treat behavioral health conditions.